2019
DOI: 10.21037/atm.2019.11.114
|View full text |Cite
|
Sign up to set email alerts
|

The risk of coronary heart disease after diagnosis of gallbladder polyp: a retrospective nationwide population-based cohort study

Abstract: Background: To assess the subsequent risk of coronary heart disease (CHD) after the diagnosis of gallbladder polyp (GP).Methods: We identified 2,815 GP patients aged ≥20 years from the Longitudinal Health Insurance Database between 2000 and 2011 and followed up the patients until the occurrence of CHD or the end of 2011, the patient would be censored in the occurrence of death, missed information, or withdrawal from the NHI. We selected 11,260 non-GP subjects by 4:1 randomly matching with the case cohort accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
6
1
1
Order By: Relevance
“…On the other hand, it may be due to cholesterol deposition in the blood, similar to the formation of atherosclerotic plaque [26]. GBP has been con rmed to be associated with increased risk of coronary heart disease [24]. In the present study, however, we found no association between lipid level, FBG, blood pressure and the risk of GBP by multilevel mixed-effects logistic regression analysis.…”
Section: Declarations Ethics Approval and Consent To Participatecontrasting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, it may be due to cholesterol deposition in the blood, similar to the formation of atherosclerotic plaque [26]. GBP has been con rmed to be associated with increased risk of coronary heart disease [24]. In the present study, however, we found no association between lipid level, FBG, blood pressure and the risk of GBP by multilevel mixed-effects logistic regression analysis.…”
Section: Declarations Ethics Approval and Consent To Participatecontrasting
confidence: 86%
“…Gallbladder mucosa esteri es sterols, absorbs lipids, and synthesizes triglycerides and cholesterol to form cholesterol crystals [24,25]. On the other hand, it may be due to cholesterol deposition in the blood, similar to the formation of atherosclerotic plaque [26].…”
Section: Declarations Ethics Approval and Consent To Participatementioning
confidence: 99%
“…We found that the presence of GB polyps alone was associated with a 42.5 % increase in the risk of developing IHD compared with a non-polyp control group. To our knowledge, only one other report has described a relationship between GB polyps and CVD [12]. However, in this latter study, the authors did not fully assess IHD-related risk factors to su ciently show a causal relationship between GB polyps and IHD.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies suggested that the presence of GB polyps is closely associated with insulin resistance, obesity, and cardiovascular disease (CVD) [11,12]. Hence, GB polyps and IHD may share common risk factors; however, few studies have explored the relationship between these two conditions [13].…”
Section: Introductionmentioning
confidence: 99%
“…(2019 г.) оценили риск развития ишемической болезни сердца (иБс) после постановки диагноза полипов Жп в общенациональном популяционном 11-летнем когортном исследовании 2815 пациентов с полипами Жп и 11 260 лиц без полипов, сопоставимых по полу и возрасту [36]. в когорте пациентов с полипами Жп определен более высокий риск развития иБс, чем у контрольной когорты (11,1 случая против 8,07 случая на 1 тыс.…”
unclassified